Turbo iterative acquisition algorithm for satellite high-mobility DSSS signal - Chunxiao JIANG; Jiawei WANG (Tongxin xuebao)
To solve the problems of the low acquisition probability and high computational complexity in satellite high-mobility communications, a new factor graph was designed for acquisition of the high-mobility direct sequence spread spectrum (DSSS) signal, where time-varying Doppler rates were modeled by the random walk model.Based on the proposed factor graph, the turbo iterative DSSS signal acquisition algorithm was proposed.In the Doppler-estimation loop, the negative influence of Doppler frequency offsets and Doppler rates could be eliminated effectively.Then in the code-detection loop, constraints of each chip was used to recover the received signal, to achieve DSSS signal acquisition.Simulation results show that the proposed algorithm is capable of improving the acquisition performance at less 1.3 dB with low computational complexity.